Genetic variability, inter-character correlation, and stability performance in cowpea for drought tolerance - Sansa, O.O.; Ariyo, O.J.; Ayyo-Vaughan, M.A.; Ekanem, U.O.; Ntukidem, S.O.; Abberton, M.T.; Oyatomi, O.A. (2025)
Drought has consistently threatened cowpea [Vigna unguiculata (L.) Walp] production, and it has become important to identify drought-tolerant, stable, and high-yielding accessions from cowpea germplasm to accelerate breeding of new drought-tolerant varieties for sub-Saharan Africa (SSA). This study assessed 112 cowpea accessions for drought tolerance and yield stability across three locations in 2 years using an 8 × 14 Alpha lattice design replicated thrice. Data collected were subjected to combined analysis of variance, broad-sense heritability, phenotypic, and genotypic correlations. Yield stability was assessed through the Additive Mean and Multiplicative Interaction (AMMI) and Genotype and Genotype × Environment (GGE) Biplot techniques. Significant variations were found among the accessions across the test environments for measured traits and reduction of grain yield due to water-stress. Genotypic correlations were higher in all the locations and environments. AMMI and GGE Biplot analysis both identified TVu-74 as the highest yielding accession and TVu-9913 as the most stable accession. Notable differences in response to drought stress indicated genetic variability and allowed the selection of drought tolerant accessions. The identified high-yielding and stable accessions could serve as potential parents in breeding climate-resilient cowpea varieties for SSA.